Dust bunny wants a friend - Hevron, Amy (New York : Schwartz & Wade Books, 2019)
A lonely dust bunny tries to make friends with passing creatures with no success, until a broom sweeps him under the bed and he finds more friends like him.
Keywords: Rabbits -- Fiction; Dust -- Fiction; Friendship -- Fiction; Rabbits -- Fiction; Dust -- Fiction; Friendship -- Fiction